Addiction as a System Failure: “Drug Abuse in Youth of Vadodara” - Toshniwal, Seema; Toshniwal, Dr. Pawan; Raj Sharma, Akshata Thorat, Khushali Sharma, (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Adolescence is a transitional stage generally occurs during the period from puberty to adulthood. It offers opportunity for growth in aptitude, independence, self-respect and relationship, but simultaneous there are associated great risks. Drug abuse is one of the alarming risk among adolescents. Drug abuse is a multifarious observable fact, which has diverse social, cultural, biological, environmental and financial aspects. This study is design to find the sources of knowledge, reasons and prevalence of drug abuse among the youth of Vadodara. Method: Youth population of school and college of Waghodia and Piparia area of Vadodara city, belongs to age group (16-22 years) has been surveyed for the drug abuse using pre-defined questionnaire format. Total 500 participate are there out of which 400 from school and 100 are from college. The data was compiled in excel to get a survey results and represented as percentage of the target population. Results: From the survey it was observed that 58% media is responsible for the knowledge of drug abuse in youth and about 70% peer pressure in school students, while 60 % pleasure feeling in college students is the reason for drug abuse. Conclusion: Overall drug abuse among school and college students i.e. age group 16 to 22 years is about 18%. By effective health education program and counseling in middle and late adolescent age group in schools and college can control the increasing behavior drug abuse.